2014
DOI: 10.9734/ejmp/2014/11246
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Anti-diarrhoeal Properties of Methanolic Leaf Extract of Maerua crassifolia Forssk

Abstract: This work was carried out in collaboration between all authors. Author GCA designed and managed the literature searches. Authors GCA and JLA carried out the antidiarrhoeal study.Author AUO wrote the first draft of the manuscript. Author BCE wrote the protocol and performed the statistical analysis. Author JAI carried out the Phytochemical analysis.All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
2
10
0
2
Order By: Relevance
“…[34][35][36] M. subcordata appears to possess marked antidiarrheal effects, which could be due to the possible presence of gut-relaxant constituent(s). In line with our findings, Akuodor et al 12 reported antidiarrheal effects of the methanol-leaf extract of a similar species, M. crassifolia, with a proposed mechanism of action linked partly to direct inhibitory effects on the propulsive movement of GI-tract smooth muscle. 12 Further tests that were intended to explain the possible mechanism(s) interestingly show that the plant extract showed biphasic effects: at lower doses (0.01-0.1 mg/mL), the extract demonstrated a stimulant effect on the basal contractions of spontaneously contracting rabbit jejuna, followed by antispasmodic effect at higher doses (0.3-1 mg/mL).…”
Section: Discussionsupporting
confidence: 92%
“…[34][35][36] M. subcordata appears to possess marked antidiarrheal effects, which could be due to the possible presence of gut-relaxant constituent(s). In line with our findings, Akuodor et al 12 reported antidiarrheal effects of the methanol-leaf extract of a similar species, M. crassifolia, with a proposed mechanism of action linked partly to direct inhibitory effects on the propulsive movement of GI-tract smooth muscle. 12 Further tests that were intended to explain the possible mechanism(s) interestingly show that the plant extract showed biphasic effects: at lower doses (0.01-0.1 mg/mL), the extract demonstrated a stimulant effect on the basal contractions of spontaneously contracting rabbit jejuna, followed by antispasmodic effect at higher doses (0.3-1 mg/mL).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that the ethanol leaf extract of P. kotschyi contain antidiarrheal properties. Previous report on the phytochemical screening of P. kotschyi leaves has shown the presence of alkaloids, tannin, cardiac glycosides, steroids, flavoniods and saponins (Akuodor et al, 2014). Plants containing these secondary metabolites have been reported to possess antidiarrhoeal activities.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were sacrificed 30 min later and gastrointestinal tract removed. The distance travelled by the marker (charcoal meal) from the pylorus to caecum was measured and expressed as the percentage of the total length of the small intestine (Abere et al, 2010;Akuodor et al, 2014).…”
Section: Intestinal Transit Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional medicine, the leaves are used for the treatment of some diseases including analgesic, anti-inflammatory, antipyretic, antibacterial and antioxidant, antimalarial, Phytochemical and antidiarrhoea Chilaka et al, 2015;Akuodor et al, 2014a;Akuodor et al, 2014d). In other pharmacological studies, the leaf extract has shown to have effects against gastrointestinal and toothache diseases (Rahman et al, 2004;Idris-Usman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%